Design Appropriateness of Boat Lift Net Based on Archipelagic Fishing Port of Karangantu - Mizan Muhammad Toyyibun (Jurnal Perikanan dan Kelautan, 2020)
Boat lift net fishing fleets in Archipelagic Fishing Port of Karangantu were built traditionally and does not have design drawings. The boats are doing its fishing activities as usual although hadn’t preliminary design. This research aims at analyzing the design appropriateness of boat lift net compliment to the static gear vessel in Indonesia. The survey method with purposive sampling is applied in the research. The research is done in Archipelagic Fishing Port of Karangantu on July until October 2019 with identification the compartments of the boat and direct measurements of the boat. The result shows that the main dimensions ratio and coefficient of fineness of boat lift net has been appropriate as static gear vessel for fishing activities. The hull form of the boats are round bottom and U-bottom. The stern of boats is flying deck added-transom, and using V-type raked bow.